Small animal ECGs : an introductory guide - Martin, Mike W. S. (Chichester, West Sussex, UK ; Ames, Iowa : John Wiley & Sons Inc., 2015)
"Small Animal ECGs: An Introductory Guide provides all the information that veterinarians need when using electrocardiography techniques for the first time"--Provided by publisher.
ECG characteristicsClinical findings; Ventricular standstill; ECG characteristics; Clinical findings; Asystole; Chapter 8 Changes in the P-QRS-T morphology; Wandering pacemaker; ECG characteristics; Changes associated with chamber enlargement; Left atrial enlargement; Right atrial enlargement; Left ventricular enlargement; Right ventricular enlargement; Low-voltage QRS complexes; ECG characteristics; Electrical alternans; Q-T interval abnormalities; S-T segment abnormalities; Abnormalities of the T wave; Hyperkalaemia; ECG characteristics; Part 3 More advanced electrocardiography.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Veterinary electrocardiography; Electrocardiography -- veterinary; Animals, Domestic; Veterinary electrocardiography; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry; Animals, Domestic; Electrocardiography -- Veterinary; Veterinary electrocardiography; Electronic books